Partial adrenal suppression with prolonged use of depo-provera / Nur Aisyah Zainordin, Fatimah Zaherah Mohd Shah and Rohana Abdul Ghani. - Zainordin, Nur Aisyah; Mohd Shah, Fatimah Zaherah; Abdul Ghani, Rohana (Universiti Teknologi MARA Cawangan Selangor, 2019)
A 49-year old patient presented with symptoms of adrenal suppression following an attempt to withdraw Depo-Provera or Depot Medroxyprogesterone Acetate (DMPA) injection. She had been receiving DMPA injections for the past 16 years for contraception. She was initially prescribed DMPA by her gynaecologist but later on began obtaining the medication directly from a private pharmacy without prior consultation from her gynaecologist. Clinically, she had been experiencing significant weight gain and appeared cushingoid. Blood investigations confirmed partial adrenal suppression with presence of an adrenal incidentaloma. This case reports a known side effect of DMPA but occurring at a much lower dose than previously described. It also highlights the need to increase the awareness of the insidious side effect of DMPA and to avoid unsupervised use of the drug.